The in fieri process of the effective integration of the principle of gender equality in the Court culture according 2030 Agenda for Sustainable Development - Melado Lirola, Ana Isabel (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
The trajectory towards gender equality is tortuous. The clarity of the rules and the forcefulnessof the arguments, even more often than expected, are dismantled at the speed of a simple clickwhen the jurists who know and work with real cases are unable to grasp the true meaning oflegal norms and oppose resistance to the deployment of the legitimate rights and interests ofwomen due to an erratic judicial culture that resists legal, economic and social evolution inaccordance with the Law. The question to rethink then is, what is the reason for this gapbetween theory and reality that, moreover, legally does not occur in other legal fields?
Keywords: Gender equality; Court culture; fundamental rights; ClosinGap; 030 Agenda for Sustainable Development; NU